Revisiting the behavior–emissions link: A multiplicative modeling approach with large-scale mobile data - Yusi Luo; Dong Zhang; Ping Huang; Yongqi Hou; Pengjun Zhao; Ling Li (Travel Behaviour and Society, 2026)

Hydrologic–anthropogenic mismatch modulates carbon–nutrient stoichiometric instability in an integrated agriculture–aquaculture watershed of southern China - Yezhao Cai; Nian She; Kairong Lin; Pengjun Li (Journal of Hydrology, 2026)

Rutin-grafted Dendrobium officinale polysaccharides: Preparation, characterization, and protection against exercise-induced oxidative stress and inflammation - Minda Zhang; Haishen Li; Jing Xu; Yaxin Zheng; Pengjun Lu; Zhenhao Li; Chongbo Sun; Jian Sun; Zhian Wang (Food Bioscience, 2026)

Interfacial engineering of upconversion nanoplatforms for optical tracking and overcoming biological barriers in RNAi-based pest resistance management - Bin Li; Jinhao Sun; Fei Wang; Guangyu Zhang; Guangwei Ren; Xiangwei You; Pengjun Xu; Yahui Yang; Chenyu Su (Chemical Engineering Journal, 2026)

Nanostructured Fe2(MoO4)3 cathodes: Enhancing ion and electron kinetics for high-rate and low-temperature sodium-ion batteries - Ting Zhao; Hang Liu; Gacao Dou; Dongting Zhang; Junqiang Qiao; Juan Yang; Pengjun Ma; Cuiying Lu; Hongxia Li; Hongruo Ma; Kunjie Wang; Bingjun Yang (Chemical Engineering Journal, 2026)

Integrative analysis of Huangjing-Gegen compatibility in treating COPD: a network pharmacology, molecular docking, and experimental study - Shaoqing Zhu; Jiaruo Li; Lin Chu; Yunpeng Zhu; Wei Wang; Man Wang; Zhenhua Zhu; Fei Mao; Pengjun Liu; Ying Chu (Natural Product Research, 2026)

Effects of affordable housing transition on residents' activity-travel behavior in Shenzhen: Evidence from longitudinal mobile phone data - Ling Li; Ping Huang; Yusi Luo; Pengjun Zhao (Journal of Transport Geography, 2026)

Evolutions of tidal flats and tidal creeks under geomorphological and eco-hydrological controls:A case study in the Yellow River Delta, China - Teng Su; Yan Li; Hongyuan Shi; Pengjun Yin; Tao Lu; Qing Wang; Qiuyu Song (CATENA, 2026)

A Data-Driven Framework for Detecting Unsafe Ship–Bridge Passages Based on AIS Trajectories - Qiyang Li; Hongzhu Zhou; Jiao Liu; Yibing Wang; Manel Grifoll; Pengjun Zheng (Journal of Marine Science and Engineering, 2026)
Ship–bridge collisions in cross-sea bridge waterways are rare but potentially catastrophic events, making conventional accident-based risk assessment difficult to implement effectively. Existing AIS-based indicators capture vessel behaviors but insufficiently quantify bridge-passage safety margins, especially dynamic aspects such as crossing posture and readiness prior to bridge transit. To address this limitation, this study proposes a data-driven framework for detecting unsafe ship–bridge passages using two bridge-passage-oriented surrogate safety measures (SSMs) and extreme value theory (EVT). The Bridge-passage Lateral Clearance Margin (BLCM) quantifies the effective lateral safety margin retained during the realized bridge-crossing stage, while the Bridge-passage Readiness Lead Time (BRLT) measures how early a vessel becomes stably prepared for bridge passage before crossing. The Peaks Over Threshold (POT) model is first used to characterize the marginal extremes of the two indicators, and a bivariate threshold exceedance model (BTE) is then established to examine their joint risk behavior. Case studies of the Jintang Bridge and Zhoudai Bridge waterways demonstrate that the proposed framework can effectively screen and identify trajectories with unsafe or margin-deficient bridge-passage characteristics. The results show that unsafe passages are typically associated with both reduced lateral clearance and insufficient preparation time, and that joint modeling of the two indicators improves risk identification performance. The findings suggest that ship–bridge risk is better interpreted from the perspective of passage quality deficiency rather than simple geometric proximity. The proposed framework provides an interpretable tool for retrospective unsafe passage screening, traffic monitoring support, and post-event safety analysis in complex bridge waterways.

Identification of tomato leaf miner secretory proteins and their roles in influencing plant defenses - Yumei Dong; Guolan Wu; Qiuyun Zhang; Zhili Zhao; Yunhua Zhang; Qian Li; Chuanlin Yin; Pengjun Zhang (Insect Biochemistry and Molecular Biology, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

Quantifying ship-bridge collision risk through extreme value theory: a new methodological framework - Xi Chen; Hongzhu Zhou; Meng Li; Manel Grifoll; Yusheng Zhou; Jiao Liu; Pengjun Zheng (Ocean Engineering, 2026)

Enhanced defluoridation using covalently bonded organosilicon-bimetallic composite coagulants: Al-Mg and Al-Fe driven divergence in hydrolysis speciation and active site substitution pathways - Yahua Zhou; Zhiyu Li; Pengjun Zhang; Yanli Kong; Jiangya Ma (Water Research, 2026)

Unrevealing the adaptivity of container shipping network during disruption events by AIS trajectory data - Zhangyuan He; Pengjun Zhao; Guangyu Huang; Zhaoxiang Li; Zhucheng Huang; Yingnan Niu; Caixia Zhang (Ocean & Coastal Management, 2025)

A Carbon Fiber-Reinforced Backfill Composite with Self-Sensing Capability for Mine Stability Monitoring - Bozhi Zhao; Shan Ning; Jingmin Xu; Tianyu Li; Wei Luo; Pengjun Gao; Weibing Zhu (Rock Mechanics and Rock Engineering, 2025)

Bridging divides: The impact of subway accessibility on income segregation in Beijing - Jiangming Liang; Ling Li; Pengjun Zhao (Transportation Research Part D: Transport and Environment, 2025)

Impact of Russia–Ukraine conflict on global crude oil shipping carbon emissions - Di Lyu; Pengjun Zhao; Weiwang Zhu; Weifeng Li; Yingkai Ling; Liang Pang; Shiyi Zhang; Yongjian Xu (Journal of Transport Geography, 2025)

Native mid-gut bacterial community increases resistance to nucleopolyhedrovirus in the cotton leafworm - Tong Li; Yueli Jiang; Yunhui Zhang; Yuqing Wu; Kenneth Wilson; Pengjun Xu (Pesticide Biochemistry and Physiology, 2025)

Mobility constraints of residents in marginal rural areas of megacities: Evidence from Beijing, China - Yu Zhao; Gou Yingrui; Li Moru; Zhao Zhifeng; Zhao Pengjun (Journal of Transport Geography, 2025)

GeoAvatar: A big mobile phone positioning data-driven method for individualized pseudo personal mobility data generation - Peiran Li; Haoran Zhang; Wenjing Li; Dou Huang; Zhiling Guo; Jinyu Chen; Junxiang Zhang; Xuan Song; Pengjun Zhao; Jinyue Yan; Shibasaki Ryosuke; Noboru Koshizuka (Computers, Environment and Urban Systems, 2025)

Impact on nonlinear runoff of LID facilities and parameter response in the TVGM model - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiang Wang; Wei Luo; Jianliang He; Jun Xia (Journal of Hydrology, 2025)

Subway expansion, residential relocation, and travel behavior: Causal evidence from China - Yiru Tan; Pengjun Zhao; Ling Li (Journal of Transport Geography, 2025)

New perspectives on urban stormwater management in China, with a focus on extreme rainfall events - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiuling Chen; Qiang Wang; Jun Xia (Natural Hazards, 2025)

Preparation of thermally sensitive ceramics by co-precipitation of mixed acid-soaked spent LIBs: Experimental methods, structure and mechanism - Ni Ai; Wenye Deng; Yi Liu; Yan Xue; Jinyang Li; Kai Ding; Pengjun Zhao; Aimin Chang; Penggao Liu; Yongxin Xie (Journal of Environmental Chemical Engineering, 2025)

Exploring collective activity space and its spatial heterogeneity using mobile phone signaling Data: A case of Shenzhen, China - Juan Li; Pengjun Zhao; Mengzhu Zhang; Yiling Deng; Qiyang Liu; Yanzhe Cui; Zhaoya Gong; Juan Liu; Wenchang Tan (Travel Behaviour and Society, 2025)

Attribution analysis of urban social resilience differences under rainstorm disaster impact: Insights from interpretable spatial machine learning framework - Tianshun Gu; Hongbo Zhao; Li Yue; Jiaojiao Guo; Qinyu Cui; Junqing Tang; Zhaoya Gong; Pengjun Zhao (Sustainable Cities and Society, 2025)

Predicting human mobility flows in response to extreme urban floods: A hybrid deep learning model considering spatial heterogeneity - Junqing Tang; Jing Wang; Jiaying Li; Pengjun Zhao; Wei Lyu; Wei Zhai; Li Yuan; Li Wan; Chenyu Yang (Computers, Environment and Urban Systems, 2024)

Analyzing foreland dynamics in China's port clusters under global major events (2019–2022) by AIS trajectory data - Zhangyuan He; Pengjun Zhao; Shiyi Zhang; Zhaoxiang Li; Guangyu Huang; Caixia Zhang; Yingnan Niu (Ocean & Coastal Management, 2024)

Biomolecule-regulation of fluorescent probe signaling: Homogeneous rapid portable protease sensing in serum - Yalan Zhu; Pan Feng; Pengjun Jiang; Kai Li; Ke Huang; Jie Chen; Piaopiao Chen (Analytica Chimica Acta, 2024)

Non-linear effects of CO2 emissions from road transport in port landside area - Zhaoxiang Li; Pengjun Zhao; Zhangyuan He; Zuopeng Xiao (Transportation Research Part D: Transport and Environment, 2024)

Exploring interactive and nonlinear effects of key factors on intercity travel mode choice using XGBoost - Xiaowei Li; Lanxin Shi; Yang Shi; Junqing Tang; Pengjun Zhao; Yuting Wang; Jun Chen (Applied Geography, 2024)

Biotechnological production of ectoine: current status and prospects - Jun Chen; Deliang Qiao; Tao Yuan; Yeyuan Feng; Pengjun Zhang; Xuejun Wang; Li Zhang (Folia Microbiologica, 2024)

Spatiotemporal characteristics and driving factors of CO2 emissions from road freight transportation - Pengjun Zhao; Zhaoxiang Li; Zuopeng Xiao; Shixiong Jiang; Zhangyuan He; Mengzhu Zhang (Transportation Research Part D: Transport and Environment, 2023)

Characterization and genomic analysis of a novel bacteriophage BUCT_49532 lysing Klebsiella pneumoniae - Guangye Zhang; Yucong Liu; Jinhong Wang; Nan Li; Pengjun Han; Yiming Chen; Weijian Xu; Changxia Liu (Virus Genes, 2023)

Effect of different multichannel ventilation methods on aerobic composting and vegetable waste gas emissions - Ruirong Li; Liang Cai; Jie Cao; Pengjun Wang; Haoli Qu; Mingjiang Chen; Yongsheng Chen (Environmental Science and Pollution Research, 2023)

Exploring the spatial characteristics of the human mobility network in rural settings of China's Greater Bay Area - Zhengying Liu; Pengjun Zhao; Qiyang Liu; Yanzhe Cui; Yuan Yang; Juan Liu; Buhui Li; Jingwei Li (Journal of Transport Geography, 2023)

Hydrophilic functionalization of rhodium metallene for saving-energy hydrogen production and sulfur recovery - Ziqiang Wang; Guanghui Yang; Pengjun Tian; Xinmiao Li; Kai Deng; Hongjie Yu; You Xu; Hongjing Wang; Liang Wang (Chemical Engineering Journal, 2023)

Circulation of Development Factors Promoted by Innovation of Land Management Under Background of Rural Vitalization: A Case Study of Tengtou Village in Zhejiang Province, China - Pengjun Wei; Yongqiang Liu; Jinlong Yan; Meiting Li; Yingnan Zhang (Chinese Geographical Science, 2023)

Enhancing catalytic performance of Fe and Mo co-doped dual single-atom catalysts with dual-enzyme activities for sensitive detection of hydrogen peroxide and uric acid - Jin Chen; Jiali Zhong; Juanhua Lai; Zoujun Peng; Tao Lian; Xiaomin Tang; Pengjun Li; Ping Qiu (Analytica Chimica Acta, 2023)

Transport Pattern and Placement Characteristics of Proppant in Different Rough Fractures - Tianyu Wang; Pengjun Zhong; Gensheng Li; Mao Sheng; Haitao Wen; Shouceng Tian (Transport in Porous Media, 2023)

Role of rural built environment in travel mode choice: Evidence from China - Zhao Yu; Peilin Li; Tim Schwanen; Pengjun Zhao; Zhifeng Zhao (Transportation Research Part D: Transport and Environment, 2023)

Anomalous Ru dissolution enabling efficient integrated CO2 electroreduction in strong acid - Beibei Sheng; Dengfeng Cao; Hongwei Shou; Wenjie Xu; Chuanqiang Wu; Pengjun Zhang; Chongjing Liu; Yujian Xia; Xiaojun Wu; Shengqi Chu; Jing Zhang; Li Song; et al. (Chemical Engineering Journal, 2023)

New Target of Oxidative Stress Regulation in Cochleae: Alternative Splicing of the p62/Sqstm1 Gene - Pengjun Li; Dan Bing; Xiaodi Wang; Jin Chen; Zhihui Du; Yanbo Sun; Fan Qi; Hanqi Chu (Journal of Molecular Neuroscience, 2022)

The Relationship of Morphological-Hemodynamic Characteristics, Inflammation, and Remodeling of Aneurysm Wall in Unruptured Intracranial Aneurysms - Qingyuan Liu; Yisen Zhang; Junhua Yang; Yi Yang; Maogui Li; Shanwen Chen; Pengjun Jiang; Nuochuan Wang; Yanan Zhang; Jia Liu; Jun Wu; Shuo Wang (Translational Stroke Research, 2022)

Optimization on Emergency Materials Dispatching Considering the Characteristics of Integrated Emergency Response for Large-Scale Marine Oil Spills - Song Li; Manel Grifoll; Miquel Estrada; Pengjun Zheng; Hongxiang Feng (Journal of Marine Science and Engineering, 2019)
Many governments have been strengthening the construction of hardware facilities and equipment to prevent and control marine oil spills. However, in order to deal with large-scale marine oil spills more efficiently, emergency materials dispatching algorithm still needs further optimization. The present study presents a methodology for emergency materials dispatching optimization based on four steps, combined with the construction of Chinese oil spill response capacity. First, the present emergency response procedure for large-scale marine oil spills should be analyzed. Second, in accordance with different grade accidents, the demands of all kinds of emergency materials are replaced by an equivalent volume that can unify the units. Third, constraint conditions of the emergency materials dispatching optimization model should be presented, and the objective function of the model should be postulated with the purpose of minimizing the largest sailing time of all oil spill emergency disposal vessels, and the difference in sailing time among vessels that belong to the same emergency materials collection and distribution point. Finally, the present study applies a toolbox and optimization solver to optimize the emergency materials dispatching problem. A calculation example is presented, highlighting the sensibility of the results at different grades of oil spills. The present research would be helpful for emergency managers in tackling an efficient materials dispatching scheme, while considering the integrated emergency response procedure.

The genome sequence of a novel RNA virus in Adelphocoris suturalis - Xinlian Li; Pengjun Xu; Xianming Yang; He Yuan; Lizhen Chen; Yanhui Lu (Archives of Virology, 2017)

Removal of Random Noise in Seismic Data by Time-varying Window-length Time-frequency Peak Filtering - Pengjun Yu; Yue Li; Hongbo Lin; Ning Wu (Acta Geophysica, 2016)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (

Molecular cloning and characterization of four heat shock protein genes from Macrocentrus cingulum (Hymenoptera: Braconidae) - Pengjun Xu; Jinhua Xiao; Li Liu; Tong Li; Dawei Huang (Molecular Biology Reports, 2010)

A thermophilic and acid stable family-10 xylanase from the acidophilic fungus Bispora sp. MEY-1 - Huiying Luo; Jiang Li; Jun Yang; Hui Wang; Yuhui Yang; Huoqing Huang; Pengjun Shi; Tiezheng Yuan; Yunliu Fan; Bin Yao (Extremophiles, 2009)